Self-evidence or pre-comprehension in the learning process of the architectonic project. Former experiences related with notions like landscape, territory or habitat - Francesconi Latorre, Rafael (UNIVERSIDAD ANTONIO NARIÑO, 2021)
This paper evaluates the potential concept of precomprehension to clarify the sense in which notions such as landscape, territory or habitat could help to foresee former experiences useful in the learning process of the architectonic project. For this purpose, sources were used from the pedagogy of architectural project and linked with philosophical ones (Heidegger, Gadamer and Habermas). Based on these sources, a concept of pre-comprehension was characterized, which helped to recognize the existence of an architectural institution and provide clues to an ex post identification of relevant former experiences, which associated results of learning with previous experiences (by linking experiences, notions, concepts and their application on architectural projects) and compared them with learning styles, as an alternative explanation of learning results.